2018
DOI: 10.1016/j.biochi.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) binding on human wild-type ISCU and Met140 variants modulates NFS1 desulfurase activity

Abstract: Human de novo iron-sulfur (Fe-S) assembly complex consists of cysteine desulfurase NFS1, accessory protein ISD11, acyl carrier protein ACP, scaffold protein ISCU, and allosteric activator frataxin (FXN). FXN binds the NFS1-ISD11-ACP-ISCU complex (SDAU), to activate the desulfurase activity and Fe-S cluster biosynthesis. In the absence of FXN, the NFS1-ISD11-ACP (SDA) complex was reportedly inhibited by binding of recombinant ISCU. Recent studies also reported a substitution at position Met141 on the yeast ISCU… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
8
12
0
Order By: Relevance
“…Our results, along with two recent studies (31,32), indicate that native ISCU2 and the ISCU2 M140I variant have similar biochemical and stability properties. First, we found that the M140I substitution does not affect the protein's secondary structure (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results, along with two recent studies (31,32), indicate that native ISCU2 and the ISCU2 M140I variant have similar biochemical and stability properties. First, we found that the M140I substitution does not affect the protein's secondary structure (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Initial radiolabeling studies suggest that Isu1 Sup increases the accumulation of persulfide species on Nfs1 similar to the addition of FXN (12,27). In contrast, two subsequent studies using standard reconstituted assays of partial reactions failed to identify a mechanism by which the human ISCU2 M140I (equivalent to Isu1 Sup ) variant could functionally replace FXN in iron-sulfur cluster biosynthesis (31,32).…”
Section: In Humans Mitochondrial Iron-sulfur Cluster Biosynthesis Ismentioning
confidence: 99%
“…[10][11][12] Zn 2+ ion has been found to completely inhibit the SDAU complex in vitro, although its activity is restored by addition of FXN. 13 Recently, crystal structures of SDA/SDAU/SDAU-Zn 2+ complexes without the key component FXN have been published, 5,14 which attributed the zinc inhibition to the sequestration of key NFS1 catalytic residue Cys381, but could not serve as template to understand the molecular roles of FXN activator. To this end, we pursued structure determination of the SDAUF complex, coupled with FXN binding studies, to decipher the FXN-mediated activation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the supporting SAXS and chemical crosslinking studies were not tested for the presence of the open form or appropriately evaluated for their ability to distinguish the closed and ready architectures (22,40,41). This model also fails to explain (i) the inherently low cysteine However, when Zn 2+ was removed by EDTA, the activity enhancement was modest and to a lower extent compared to the activating effect of FXN (43). Again, this model also neither considers the open architecture, which has been demonstrated to be the dominant SDAec species in solution, nor explains the inherently low cysteine desulfurase activity of the SDAec complex (5,18,24).…”
Section: Substitutions Have Varied Effects On the Dimeric Binding Conmentioning
confidence: 93%